The Role of Public Policy in Skills Development of Black Workers in the 21st Century - Timothy J. Bartik; Kevin Hollenbeck (W.E. Upjohn Institute for Employment Research, 2000)
This paper discusses the role of public policy in the skills development system of the U.S. It further examines the implications of that policy for the skill development and career progression of black workers. The paper describes the current "system" for skills development in the United States as a two-tiered system: The "first-chance" or conventional system allows individuals to proceed through an extensive public elementary, secondary, and postsecondary educational sector that is supplemented by private educational institutions and is followed by employer-provided job training and work experience. The "second-chance" system is designed for individuals who do not successfully traverse the first-chance system. The second-chance system includes public job training programs, public assistance, rehabilitation programs for offenders, and educational remediation. The public agency for labor market exchange, the Employment Service, has tended to play a significant role in facilitating employment in the second-chance system. Paradoxically, despite the tremendous success of the U.S. economy, including the fact that it has the world's leading level of worker productivity, there is a pervasive perception that the current system for skills development in the U.S. is failing. Lagging school achievement (particularly in urban areas), high unemployment rates for certain groups of the population, and employer concerns about the quality of entry level workers suggest that the current system may be neither efficient nor equitable. The paper starts out by considering the rationale for public policy intervention in the skills development process. It then reviews public policy at the federal, state, and local levels that fosters skills development. At the federal level, the major policy emphasis currently is the consolidation of job training and labor market exchange programs through the Workforce Investment Act (WIA). State and local entities administer federal programs, but many states have also enacted supplemental programs in the area of skills development. After examining specific federal and state/local policy, the paper reviews recent policy demonstrations in the area of skills development. The review of the evaluative evidence leads to several general "best practice" principles about content, delivery mechanisms, and administrative characteristics. The last section of the paper reviews how well federal WIA programs are likely to fare against the best practices criteria. The major thrusts in skills development policy have been accountability, market-driven choice, decentralization/devolution, emphasis on immediate work, private-sector leadership, and consolidation. The policy characteristics that are in disfavor seem to be eligibility set asides, process regulations, service delivery by administrative agencies, subsidized education and training, technical assistance, and research and development. African Americans, who reside disproportionately in urban areas and who participate in the second-chance system, will be affected by these changes in emphasis. Public policy has evolved from a top-down, centralized system with regulatory protections and emphasis on equal access to an open, decentralized system operated largely by state bureaucrats and governed by individuals at the local level who happen to take an interest and who happen to know the right individuals at the right time. Theoretical arguments can be made that the new system will be more efficient and more equitable and counterarguments can be offered that the system will result in outcomes that are highly varied across localities and racial groups.
Additional information: A revised version of this paper appears in Cecilia Conrad, ed. 2004. Building Skills for Black Workers: Preparing for the Future Labor Market. Washington, DC: Joint Center for Political and Economic Studies, Dallas: University Press of America, pp. 127-148.
Keywords: J0; J7; I3; 330; public policy; skill development; careers; blacks; Bartik; Hollenbeck